2021
DOI: 10.1088/1755-1315/648/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of limiting fators of RGL citrus fruit productivity (study case in Pal VII Village, Bermani Ulu Raya Subdistrict, Rejang Lebong District)

Abstract: Environmental factors, especially climate, soil and pest attack, are limiting factors in citrus production. The purpose of this study was to determine the limiting factors on RGL citrus productivity. This research was carried out in 2019 in Pal VII Village, Bermani Ulu Raya District, Rejang Lebong Regency, Bengkulu Province with seven farmers at the research location. Data was collected from primary and secondary data consist of 10 years climate data, soil characteristics and citrus pest and diseases identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…Citrus production is largely determined by the use of inputs and will also affect the amount of production costs, as well as farmers' income. The results of research by Abbas et al (2017) and Siagian et al (2021), differ from the overall results of this study, that several factors that also affect citrus production are socioeconomic factors (age, education, experience, skills and income of citrus farmers). On the other hand, natural factors (rainfall) and pest and disease attacks as well as low land fertility are also limiting factors for citrus farming productivity.…”
Section: Resultscontrasting
confidence: 99%
“…Citrus production is largely determined by the use of inputs and will also affect the amount of production costs, as well as farmers' income. The results of research by Abbas et al (2017) and Siagian et al (2021), differ from the overall results of this study, that several factors that also affect citrus production are socioeconomic factors (age, education, experience, skills and income of citrus farmers). On the other hand, natural factors (rainfall) and pest and disease attacks as well as low land fertility are also limiting factors for citrus farming productivity.…”
Section: Resultscontrasting
confidence: 99%
“…comm., September 2022). In Sumatra (Indonesia), infestation level appears to be related to fruit age/ripening status (Siagian et al, 2021).…”
Section: Background Information and Host Distributionmentioning
confidence: 99%
“…It indicated that the bioactive compounds of C. reticulata from different planting locations might differ from the same species (Abeysinghe et al 2007;Wang et al 2019;Wang et al 2020). The difference in secondary metabolites could be due to genetic variations, availability of nutrients, and environmental conditions where they are grown (Anggraheni 2021;Siagian et al 2021). In addition, the difference in the number of identified compounds may be influenced by the sensitivity of the LC-QTOF-MS/MS used.…”
Section: Identified Bioactive Compounds In Rgl Orange Extractmentioning
confidence: 99%
“…It was designated as a national superior variety by the Ministry of Agriculture of the Republic of Indonesia in 2012 because it can bear fruit throughout the year with two harvests in one year (Astuti et al 2018). In addition, RGL oranges are yellow-orange and are in great demand by local people (Siagian et al 2021). This RGL orange development program is mainly located in PAL VIII Village, Bermani Ulu Raya Sub-district, Rejang Lebong District, with an area of 200 hectares.…”
Section: Introductionmentioning
confidence: 99%